Internet of Things, Big Data, and Artificial Intelligence in The Food and Agriculture Sector - Suryari Purnama; Wahyu Sejati (International Transactions on Artificial Intelligence, 2023)
Big data often referred to as streaming data produced by the internet of things creates new options for monitoring food and agricultural processes. Along with sensors, social media big data is also playing a bigger role in the food business. The IoT, big data, and artificial intelligence are discussed in this review along with how they will impact the agri-food industry in the future. We begin with an introduction to the fields of IoT, big data, and AI before talking about how IoT and big data analysis are used in agriculture, including smart farm equipment, crop imaging using drones, and monitoring of greenhouses, food quality assessment using spectral techniques and sensor fusion, and eventually, food safety using gene sequencing and blockchain-based digital traceability. The commercial viability of applications and the outcomes of translational research are given significant consideration.